2x-(12-x)=x+7+2x

Simple and best practice solution for 2x-(12-x)=x+7+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(12-x)=x+7+2x equation:


Simplifying
2x + -1(12 + -1x) = x + 7 + 2x
2x + (12 * -1 + -1x * -1) = x + 7 + 2x
2x + (-12 + 1x) = x + 7 + 2x

Reorder the terms:
-12 + 2x + 1x = x + 7 + 2x

Combine like terms: 2x + 1x = 3x
-12 + 3x = x + 7 + 2x

Reorder the terms:
-12 + 3x = 7 + x + 2x

Combine like terms: x + 2x = 3x
-12 + 3x = 7 + 3x

Add '-3x' to each side of the equation.
-12 + 3x + -3x = 7 + 3x + -3x

Combine like terms: 3x + -3x = 0
-12 + 0 = 7 + 3x + -3x
-12 = 7 + 3x + -3x

Combine like terms: 3x + -3x = 0
-12 = 7 + 0
-12 = 7

Solving
-12 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| A=1/2x22x7 | | .50=lny | | M/pi=3 | | -38-7k=8(k+4) | | 3=q | | x+3/5=-6 | | t+75=-225 | | 9/16-5/12 | | x/3-7=7 | | 7(x+8)=3(x+2)+4x | | x/20-1/5=35 | | 3x+5=-7x-2q | | log[5](15x+5)-log[5](x)=2 | | -68=-20-8r | | 6-m/8=20 | | 50+2x=100 | | ((x^2)-(2x))=15 | | 4(4c-1)-6=12c+6 | | 4=a/3-4 | | 6*x-8*x=12 | | 9=x+8 | | 15m^2-39m-18= | | -8z-2z=-2z-4-7z | | 2-a/-3=9 | | 4m^2+11m-38=0 | | 9=m/4 | | 4(1.5x+9)=2x+25 | | 2/5m-1/5=5/30 | | 1.5/6.5=y/39 | | 39=-13x | | 1/2u-8/7=-4/5 | | -42n=2478 |

Equations solver categories